Effect of Fluoride Varnish on Enamel Remineralization in Anterior Teeth with Molar Incisor Hypomineralization - Restrepo, Manuel [UNESP]; Jeremias, Fabiano [UNESP]; Santos-Pinto, Lourdes [UNESP]; Cordeiro, Rita C. L. [UNESP]; Zuanon, Angela C. C. [UNESP] (Journal Pedodontics Inc, 2016)
Objective: The objective of this study was to investigate the effect of fluoride varnish on remineralization of anterior teeth affected by Molar-Incisor Hypomineralization (MIH) by means of Quantitative Light-Induced Fluorescence- QLF. Study design: Fifty-one healthy 9 - 12- year-old children were selected according to different clinically diagnosed levels of MIH, proposed by the European Academy of Pediatric Dentistry (2003) (considering the most severe lesion per patient, n= 51 lesions), and randomly divided into two groups: (1) four applications of 5% NaF varnish, with one-week interval, and (2) usual home care- control. At each visit, the mean change in fluorescence and area of lesion were measured by QLF. The data were analyzed by repeated measures ANOVA and Tukey's test. Results: All patients showed enamel alterations in first permanent molars and incisors, frequently with two molars affected by MIH (41.1%). There was no statically significant difference in the mean of fluorescence and area of lesion between groups over the studied time. Conclusion: We observed no favorable effect on the remineralization of MIH lesions in anterior teeth after four applications of fluoride varnish.
Keywords: Fluorescence; Fluoride; Molar Incisor Hypomineralization; Tooth remineralization